Humor and Irony in Jorge Luis Borges from a Metaphysical Perspective - Abello Rayo, Luis Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The deep influence of philosophy in Jorge Luis Borges is widely known. The relationship between philosophy and literature is investigated in this paper as a way to present how Borges converts literature as an extension of philosophy.Through the concepts of humor and irony, works of this Argentinian writer  are analyzed here to establish a vision of its metaphysics. The purpose of this paper is to reflect on how short stories of the Argentinian writer converge within the frameowrk of the relationship between philosophy and literature, seen from irony and humor. Borges must be understood from different approaches;  oneof them is certainly philosophy. From there, a relationship is established between philosophy and literature which analyzes in depth metaphysics and irony in his short stories. As Borges’ writing is understood, in some way, by the prism of philosophy, this paper demonstrates an analytical approach to the irony and humor as part of the metaphysical point of view.